(untitled) (UNIZIK Journal of Marketing, 2025)
This study examined the impact of digital marketing strategies on sales performance and brand reputation in the Nigerian hotel industry. The rapid evolution of digital platforms has reshaped consumer behavior, making it critical for hotels to adopt effective digital marketing techniques to remain competitive. Despite the growing reliance on digital marketing, the extent to which these strategies influence sales performance and brand reputation in the Nigerian context remains underexplored. The objective of this research is to assess the effectiveness of digital marketing tools, such as social media campaigns, search engine optimization (SEO), and online advertising, in improving sales performance and enhancing brand reputation among Nigerian hotels. The study employed a mixed-method approach, combining qualitative interviews with hotel managers and guests. The findings revealed a positive correlation between the adoption of tailored digital marketing strategies and increased sales performance, as well as a notable improvement in brand perception. However, challenges such as inconsistent internet access, limited technical expertise, and low customer engagement were identified as barriers to full utilization of digital marketing in the sector. Based on these findings, it is recommended that Nigerian hotels invest in targeted digital marketing training for staff, improve internet infrastructure, and engage in more personalized marketing efforts to strengthen their online presence. Additionally, hotels should leverage data analytics to refine strategies and enhance customer engagement, ultimately improving both sales performance and brand reputation. The study highlighted the growing significance of digital marketing in the hospitality sector and offers practical suggestions for hotel managers seeking to thrive in a competitive digital landscape.